THE INFLUENCE OF STRATEGIC HR PRACTICES ON ORGANIZATIONAL PERFORMANCE IN MICRO COMPANIES - Emil Knezović (Economic Review)
The research in human resource management (HRM) field has evolved in past couple decades. By observing human resources (HR) as one of the most important assets in the business, it is obvious that it represents a key to business success or failure. By reviewing the literature, one cannot neglect that there is one serious gap in HRM research which relates to micro companies. This study aims to reduce that gap by examining 107 micro companies in relation to strategic HR practices and organizational performance. Results show that there is no enough evidence to support positive and significant relationship between strategic HR practices and organizational performance in micro companies.